Plant systematics : (Sinauer Associates, 2002)
A much expanded CD-ROM is included, containing over 2,200 colour photographs illustrating the diagnostic characters of plant families covered in the text. Appropriate for any course devoted to the systematics of plants, this text assumes no prerequisites other than introductory botany or biology.